Uji Kinerja Pompa Hidram - Nurfauzan, M.; Zulkarnain, Iskandar; Ridwan, Ridwan; Suharyatun, Siti (Jurnal Agricultural Biosystem Engineering, 2022)
Hydram pump is a pump that utilizes potential energy sources of water to be flowed. the ideal hydram pump component that can be used to raise the maximum water is not known for sure. This study aims to test the performance of a hydraulic ram pump with one suction valve with a diameter of 0.5 inches and two exhaust valves with a diameter of 0.5 inches to obtain the maximum pump output height, the highest discharge and efficiency as well as the optimal pump input height. The research was conducted using 3 variations of inlet pipe height (H), namely 1 m, 2 m and 3 m. Each inlet pipe height is varied by 5 outlet pipe height (h) with h=H+(2^n x0.25) with n=0 – 54. From the test results, the highest output discharge is 5 liters/minute at the inlet pipe height H = 3 m and the height of the outlet pipe is h = 3.25 meters. The highest efficiency is 17.21%. obtained at the height of the inlet pipe H = 3 m and the height of the outlet pipe is 3.25 meters. At H = 1 m the pump can raise water to a maximum of 4.83 m, at H = 2 m it can raise water to a maximum of 10 m and at a water source height of 3 m it can raise water to a maximum of 18.44 m. Keywords: Efficiency, Inlet Pipe Height, Outlet Pipe Height, Water Energi.